Impact of Pre and Post Budget on Stock Market Volatility Between 2001 to 2011 - Varadharajan, P.; Vikkraman, Dr. P. (Journal of Contemporary Research in Management (JCRM), 2013)
The stock market is witnessing heightened activities and is increasingly gaining importance. In the current context of globalization and the subsequent integration of the global markets this paper captures the trends, similarities and patterns in the activities and movements of theÂ  Indian Stock Market from 2002 to 2011. This paper explores the impact of budget on stock market volatility and analyses how returns vary with it. Another important analysis done is to find the volatility of different months for a period of ten years for four major indices in India. Analysis of BSE, NSE market capitalisation is also done. The main aim is to help investors gain knowledge about volatility present in different months, thereby they can invest cautiously. Thus, this study helps the investors to minimize theirÂ  overall risk and maximize the return of their investment over any period of time.